Existence and Compactness Results for a System of Fractional Differential Equations. (11th July 2020) - Guendouz, Cheikh; Lazreg, Jamal Eddine; Nieto, Juan J.; Ouahab, Abdelghani
Abstract : The existence and uniqueness, boundedness, and continuous dependence of solutions for fractional differential equations with Caputo fractional derivative is proven by Perov's fixed point theorem in vector Banach spaces. We study the existence and compactness of solution sets and the u.s.c. of operator solutions.